The Ground sits fallow across the River - Branch Cultural Historical Association (2010)
In the 1930s and 1940s, during the tumultuous years of the Depression and World War II, considerable agricultural land was cleared in Branch. The Ground, just up the River from Roches Gulch, was cleared by and for war veterans returning home to Branch. This large parcel of land sits fallow today, its name an indication of the close relationship between people and land. The insert shows the Ground in the 1980s - two swaths of land separated by a row of trees.